Growth of Two Cocoa (Theobroma cacao L.) Planting Materials on Three Growing Media Composition - Fuadi Mubaroq, Zahrul; Anita-Sari, Indah; Abdul Hakim, Nurman; Nazirman, ,; Wibowo, Ari; Setyawan, Bayu (Indonesian Coffee and Cocoa Research Institute, 2023)
Seed growth and uniformity are keys in producing high quality and yield of cocoa (Theobroma cacao L.). Plant growth is influenced by internal factors (genetics)and external factors, including planting media. This study aimed to determine the effect of cocoa planting material types and planting media of cocoa seedlings.The research was conducted at Kaliwining Experimental Station, Indonesian Coffee and Cocoa Research Institute (ICCRI), Jember, Indonesia, using a split-plot group randomized design. The main plot was the planting media consisting of topsoil, topsoil and rice husk, and topsoil and manure. The subplots consisted of two types of cocoa planting material: hybrid seeds ICCRI 08H and half-sib Sulawesi 1. Each treatment was replicated three times. The results showed that the media influenced on seedling growth uniformity, plant height, stem diameter, and number of leaves. Genetic factors affect plant height and stem diameter. The interaction of media and the type of planting material affect the stem diameter and number of leaves. Cocoa seedling growth with the best plant height and stem diameter was shown in topsoil and manure media, while the response to the number of lleaves showed differences between ages and planting media used. ICCRI 08H hybrid cocoa planting material showed the highest plant height and stem diameter compared to Sulawesi 1 half-sib